FAN FICTION PHENOMENON: BETWEEN COPYRIGHT INFRINGEMENT AND REASONABLE USE IN COPYRIGHT LAW - Pranadita, Nugraha; Rahmatullah, Tansah (Universitas Muhammadiyah Tapanuli Selatan, 2023)
Fan fiction is amateur writing that imaginatively recreates a work in pop culture while maintaining identifiable aspects of the pre-existing work. The phenomenon and popularity of fan fiction today has led to the emergence of issues related to the legality of such works in the context of Copyright Law. Is fan fiction recognized and legitimate under copyright law? Do the creators of fan fiction works have copyrights and get the same rights to obtain economic benefits from the works they create? This research uses a qualitative normative juridical research approach. The normative juridical research approach in legal research is an approach that focuses on analyzing the applicable legal regulations. Support for the existence of fan fiction is based on the existence of the fair use doctrine in the United States Copyright Law. In the context of Indonesian law, these works of fan fiction fall into the category of adapted works in accordance with Law Number 28 of 2014 concerning Copyright. Fan fiction works that are widely circulated on the internet have no commercial opportunities because they are freely accessible and have no opportunity for profit. Fan fiction authors often include a 'disclaimer' at the top of their work to say that they receive no monetary profit or benefit from its production. One suggested solution is to use an alternative license agreement. In this case, the current doctrine of fair use may not be sufficient to cover the beneficial and non-commercial use in the form of fan fiction. Therefore, the expansion of fair use to cover such uses may be proposed as a possible solution.